2021
DOI: 10.1532/hsf.4073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine on The Neuroglobin Expression in Elderly Patients With Minimally Invasive Coronary Artery Bypass Graft Surgery

Abstract: Background: To study the effect of dexmedetomidine (Dex) on the expression of Neuroglobin (Ngb) and postoperative cognitive function in elderly patients undergoing minimally invasive coronary artery bypass surgery. Methods: Forty patients, who underwent elective minimally invasive off-pump coronary artery bypass grafting in our hospital from January 2018 to December 2019, were randomly divided into the Dex group (N = 20) and control group (N = 20). Venous blood samples were taken to determine the expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity: I 2 = 92%, 2 = 51.7988, p < 0.01 Ammar [30] Azeem [31] Balkanay [32] Bulow [33] Chi [34] Cho [35] Corbett [36] Cui [37] Djaiani [38] Dong [71] Elgebaly [40] Elgebaly [39] Gao [74] Goksedef [41] Huang [44] Khalil [47] Khalil [46] Kim [48] Kim [73] Li [50] Likhvantsev [51] Liu [52] Maldonado [53] Massoumi [54] Mogahd [55] Momeni [56] Park [57] Shehabi [59] Shi [retracted] Shokri [60] Soh [63] Subramaniam [64] Tosun [65] Turan [11] Wu [66] Zhai [68] Zi [70] Total . Evaluations (GRADE) organisation [13], and assessed for interstudy heterogeneity using I 2 statistics, s-squared values and p values from the chi-squared test, as well as visually inspecting forest plots [14].…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Abd Aziz [28] Abdel Meguid [29] Ammar [30] Azeem [31] Balkanay [32] Bulow [33] Chi [34] Corbett [36] Cui [37] Djaiani [38] Dong [71] Elgebaly [40] Elgebaly [39] Goksedef [41] Gong [43] Herr [42] Huang [44] Karaman [45] Khalil [47] Kim [73] Leino [49] Li [50] Likhvantsev [51] Liu [52] Maldonado [53] Masoumi [72] Massoumi [54] Mogahd [55] Momeni [56] Park [57] Qin [58] Shehabi [59] Shi [retracted] Shokri [60] Shu [62] Soh [63] Tosun [65] Wu [66] Zhai [67] Zhou [69] Zi [70] Total . quality.…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Gao et al examined the effect of dexmedetomidine vs. control on postoperative cognitive function and neuroglobin expression following minimally invasive off-pump CABG. It should be noted that off pump CABG is prone to intra-operative oxygen desaturation and associated with POCD, given the requirement for single lung ventilation ( 182 , 183 ). The use of dexmedetomidine was associated with a lower incidence of POCD at POD7 and POD30 ( p < 0.05) and higher MMSE scores (Mean ± SD) at POD7 (24.8 ± 1.3 vs. 20.5 ± 1.4; p < 0.001) and POD30 (28.3 ± 1.5 vs. 24.2 ± 1.2; p < 0.001).…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 99%
“…Neuroglobin is a hypoxia inducible protein which is highly expressed in the frontal lobes and hypothalamus. It has a high affinity for oxygen, increasing oxygen delivery to the brain ( 183 , 184 ). These results suggest that neuroglobin may be neuroprotective for postoperative cognitive impairment.…”
Section: Pathophysiology Of Postoperative Cognitive Dysfunction Follo...mentioning
confidence: 99%